The Latin American Solidarity Organization (Laso) through the Information Bulletin of Its Organizing Commitee (1966-1967) - Calvo, Patricia (Revista de Historia Social y de las Mentalidades, 2018)
The Latin American Solidarity Organization (LASO) was born at the end of the sixties with the objective of the liberation of the peoples of the continent and the overcoming economic, social and cultural underdevelopment, raising the armed struggle and anti-imperialism to reverse this situation. The discrepancies within the international and Latin American communism did, in the end, that the organism was disappearing, and it has been relegated to an anecdotal level in the studies on the topic. The aim is to go deeper into the role of LASO through the analysis of its information bulletin to offer a vision from inside.